Examining the impact of social media on mood and body dissatisfaction using ecological momentary assessment. Issue 5 (3rd July 2020) - Bennett, Brooke L.; Whisenhunt, Brooke L.; Hudson, Danae L.; Wagner, Allison F.; Latner, Janet D.; Stefano, Emily C.; Beauchamp, Marshall T.
Abstract: Objective: To assess the effects of social media consumption on body dissatisfaction and negative affect using ecological momentary assessment, a method of assessment over time in the participants' naturalistic environment. Participants: Woman college students ( N = 30) from a large public university participated in the study in Fall 2015. Methods: Participants were contacted via their smartphones five times per day for five days and asked to complete a battery of measures which assessed social media use, body dissatisfaction, and negative affect. Results: Results demonstrated that the number of social media sites visited was a significant predictor of body dissatisfaction while time spent using social media was not. The number of sites visited and time spent on social media were both significant predictors of general negative affect, sadness, and guilt. Conclusions: Results demonstrate the negative impact that social media use can have on body dissatisfaction and negative affect.